KESIAPAN GURU DALAM MELAKSANAKAN PEMBELAJARAN BERDIFERENSIASI PADA PENINGKATAN KEMAMPUAN NUMERASI SISWA SD/MI DI LOMBOK TENGAH - Indraswati, Dyah; Amrullah, Lalu Wira Zain; Putra, Gita Prima; Fauzi, Asri; Nurmawanti, Iva (STKIP Singkawang, 2023)
Observation results show that teachers can carry out initial assessments but have not been able to design learning strategies that suit students' learning needs. Therefore, it is necessary to carry out research regarding teacher readiness in implementing differentiated learning to improve students' numeracy abilities. This research is a quantitative descriptive study that presents conclusions based on statistical presentation. This research was carried out by surveying 16 elementary/MI schools in North Batukliang, Pujut, and Batukliang Districts which are target schools for the SAC (All Smart Children) program from INOVASI. The research subjects were 32 SD/MI teachers consisting of 2 teachers in each educational unit, namely class I and IV teachers who had implemented the principles of an independent curriculum in learning. The results of the research show that elementary/MI teachers in Central Lombok are ready and able to carry out differentiated learning that focuses on improving students' numeracy skills but still requires improvement in several aspects of each achievement indicator that has been determined.